Nishi Amane and Modern Japanese Thought - Havens, Thomas R. H. (Book collections on Project MUSE., 1970)
A nineteenth-century aristocrat, Nishi Amane (1829-1897) was one of the first Japanese to assert the supremacy of Western culture. He was sent by his government to Leiden to study the European social sciences; on his return to Japan shortly before the climactic Meiji Restoration of 1868 he introduced and adapted European utilitarianism and positivism to his country's intellectual world. To modernize, Nishi held, Japan must cast off the bonds of the Confucian world-view in order to adopt new principles of empirical scholarly investigation and new standards of self-improvement. Though a Confucian by upbringing, Nishi became thoroughly committed to Western intellectual values in his programs for the new Japanese society. In his roles of teacher, writer, and government administrator, he was influential at one of the most critical times in Japan's history.